2007
DOI: 10.1111/j.1600-0609.2007.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity upon infusion of dimethylsulfoxide‐cryopreserved peripheral blood stem cells in patients with and without pre‐existing cerebral disease

Abstract: To our knowledge, this is the first report addressing the identification of predisposing factors for DMSO-related neurotoxicty. We conclude that infusion of DMSO-PBSC can be performed safely in patients with pre-existing cerebral disease despite the rare occurrence of severe neurotoxicity. Retrospective multicenter studies are warranted to identify patients who would benefit from elaborate methods of DMSO-replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…6 These rates were not achieved in our patient, as the total dose administered was 560 mg/kg. Nevertheless, Junior et al 7 and Abdelfeki et al 8 suggested that DMSO toxicity could also be idiosyncratic.…”
mentioning
confidence: 65%
“…6 These rates were not achieved in our patient, as the total dose administered was 560 mg/kg. Nevertheless, Junior et al 7 and Abdelfeki et al 8 suggested that DMSO toxicity could also be idiosyncratic.…”
mentioning
confidence: 65%
“…As the clinical symptoms appeared during or soon after the Schlegel et al 2009), so bringing the total to 27 case studies. Many of these indicated the observed reactions were tenuously or convincingly associated with the DMSO (Corso et al 1993;Zenhausern et al 2000;Hoyt et al 2000;Benekli et al 2000;Windrum and Morris 2003;Bauwens et al 2005;Chen-Plotkin et al 2007;Mueller et al 2007;Junior et al 2008;Otrock et al 2008;Abdelkefi et al 2009;Ruiz-Delgado et al 2009) or the presence of lysed cells (Ruiz-Delgado et al 2009). Whilst others implicated hypothermia of the infusate (Hequet et al 2002), anaphylaxis due to DMSO (Rapoport et al 1991), the rate of infusion (Junior et al 2008) or the volume of cryopreserved stem cells (Dhodapkar et al 1994).…”
Section: Adverse Reactions In Recipientsmentioning
confidence: 99%
“…While some cells, for example fibroblasts, are easily cryopreserved other cell types like keratinocytes, hepatocytes, and cardiac myocytes do not freeze well and cell yields are often <50%. Furthermore, current opinion is that DMSO should be removed before cells are infused into patients (Caselli et al, 2009;Junior et al, 2008;Mueller et al, 2007;Otrock et al, 2008;Schlegel et al, 2009). The mechanism for DMSO cytotoxicity has not been determined, however, it is thought to modify membrane fluidity, induce cell differentiation, cause cytoplasmic microtubule changes and metal complexes (Barnett 1978;Katsuda et al, 1984Katsuda et al, , 1987Miranda et al, 1978).…”
Section: Introductionmentioning
confidence: 99%